(untitled) (Fiep Bulletin - online, 2013)
The objective of the present study is to propose an adaptation from the Model of Walton, where the criteria were transcribed in the interrogative form, and the scale of answers were converted into a Likert scale with five alternatives. The verification of the inner consistency of the instrument was achieved from the Cronbach’s alpha coefficient, which the obtained value was 0,96. Such result guarantees a very high consistency to the instrument adopted. It can be concluded that the adaptation from the Model of Walton, proposed in this study, allows, through more clarified questions and a more objective scale of answers, its application to people with low schooling level, guarantying the obtaining of reliable results without changing criteria and objectives of the original instrument.